Empowering Women in the Economic Sector through Entrepreneurship Training in Rural Areas - Luluk Indarinul Mufida; Brata, Diah Puji Nali; Lilis Rahmawati; Devlan, Alina; Mukhlisin, Mukhlisin (Bisma : Bimbingan Swadaya Masyarakat, 2025)
This study examines the impact of entrepreneurship training on the empowerment of women in Tambakboyo Village, East Java. Through a participatory action research (PAR) approach, the research explores how training programs can enhance women’s business skills, self-confidence, and income-generating capacities. The findings indicate that the training significantly improved participants' understanding of business management, financial planning, and marketing strategies. However, challenges such as limited access to capital and societal barriers persist, limiting the full potential of the trained women. The study highlights the importance of continued support through financial services, community engagement, and policy reforms to overcome these barriers. Ultimately, the research suggests that entrepreneurship training, when combined with necessary resources and societal changes, can empower rural women, fostering sustainable economic development and contributing to social change within their communities